Choledochal Cyst: Experience from A Tertiary Level Hospital of Bangladesh (IAHS Medical Journal, 2022)
Background : Choledochal cysts are rare, congenital abnormal dilatations of the intrahepatic biliary channels of uncertain origin. It may clinically manifest at any age. Biochemical tests are not diagnostic but imaging modalities help in accurate diagnosis. Surgery in the form of complete excision of the cyst with diversion is the treatment of choice and decreases the risk of dreaded complication of cholangiocarcinoma. The aim of this study is to demonstrate the sex distribution, symptomology, biochemical presentation, radiological findings and outcome of surgery in Bangladeshi population.Methods and materials: A total of 12 cases were considered for this study which included all the cases that were admitted at Bangabandu Sheikh Mujib Medical University (BSMMU) during June 2013 to May 2014. The study also covered the incidence of the type of the cyst, post-operative complications and follow up of the patient for 5 years at least.Results: 9 of the patients were female and the median age of presentation was 17. Todani type I was the most common type. Patients attended hospital with upper abdominal pain (100%) alongwith other symptoms like vomiting, jaundice, etc. S. bilirubin and alkaline phosphatase were raised in most of the patients. Radiological diagnosis was done effectively by ultrasonography, CT (Computer Tomography) scan and MRCP (Megnatic Resonance Cholangiopancreatography). All the patients underwent complete excision of the Choledochal cyst with cholecystectomy with Roux en Y hepaticojejunostomy and post-operative complications include wound infection (n=2) scar pain and recurrent cholangitis (16.67% each).Conclusion: Surgery is the treatment of choice and decreases the risk of cholangiocarcinoma. Long term follow is required in these patients.IAHS Medical Journal Vol 4(1), June 2021; 51-55